Epidemiology and return to play following isolated syndesmotic injuries of the ankle: a prospective cohort study of 3677 male professional footballers in the UEFA Elite Club Injury Study - Lubberts, B.; D`Hooghe, P.; Bengtsson, H.; DiGiovanni, C. W.; Calder, J.; Ekstrand, J. (British Journal of Sports Medicine, 2019)
Aim: To determine the epidemiology of isolated syndesmotic injuries in professional football players.